Interferons as antivirals: translating basic research into clinical application - Fish, Eleanor N. (Henry Stewart Talks, 2011)
Emerging and re-emerging virus infections globally, Time lag before a new vaccine is available during a pandemic, Antivirals that are pathogen specific lead to viral resistance, Broad spectrum antivirals needed, Interferons -alpha -beta are produced in response to all virus infections, Every cell/tissue will respond to interferon, Widespread application for all virus infections, Update interview: Consider route of administration for most effective outcome, Update interview: Prophylactic treatment in specific settings
Updated at 2021/02/20